Resistance of Winter Spelt Wheat [Triticum aestivum subsp. spelta (L.) Thell.] to Fusarium Head Blight - Chrpová, Jana; Grausgruber, Heinrich; Weyermann, Verena; Buerstmayr, Maria; Palicová, Jana; Kozová, Jana; Trávníčková, Martina; Nguyen, Quynh Trang; Moreno Amores, Jose Esteban; Buerstmayr, Hermann; Janovská, Dagmar (Frontiers in Plant Science, 2021)
Resistance to Fusarium head blight (FHB) of spelt wheat was investigated in field trials carried out at three European locations between 2016 and 2018. Resistance was assessed after artificial inoculation by visual scoring of symptoms and the determination of the contamination of grains and glumes with the mycotoxin deoxynivalenol (DON). It was found that typical spelt traits such as tall plant height, lax spikes and tough glumes play a role as passive resistance factors. Across all test environments, modern spelt varieties with a significantly reduced plant height showed a significantly higher susceptibility to FHB and a higher contamination of the grains with DON compared to old landraces/varieties and plant genetic resources. Similarly, the lowest mycotoxin level in grains were found only in old landraces and varieties, while the highest DON concentration was observed mainly in modern varieties. The results obtained can be used for the selection of suitable parental material for breeding spelt with improved FHB resistance.